Fungal Planet description sheets: 1383-1435 - Crous PW; Boers J; Holdom D; Osieck ER; Steinrucken TV; Tan YP; Vitelli JS; Shivas RG; Barrett M; Boxshall AG; Broadbridge J; Larsson E; et al. (RIJKSHERBARIUM, 2022)
Novel species of fungi described in this study include those from various countries as follows: Australia, Agaricus albofoetidus, Agaricus aureoelephanti and Agaricus parviumbrus on soil, Fusarium ramsdenii from stem cankers of Araucaria cunninghamii, Keissleriella sporoboli from stem of Sporobolus natalensis, Leptosphaerulina queenslandica and Pestalotiopsis chiaroscuro from leaves of Sporobolus natalensis, Serendipita petricolae as endophyte from roots of Eriochilus petricola, Stagonospora tauntonensis from stem of Sporobolus natalensis, Teratosphaeria carnegiei from leaves of Eucalyptus grandis x E. camaldulensis and Wongia ficherai from roots of Eragrostis curvula. Canada, Lulworthia fundyensis from intertidal wood and Newbrunswickomyces abietophilus (incl. Newbrunswickomyces gen. nov.)on buds of Abies balsamea. Czech Republic, Geosmithia funiculosa from a bark beetle gallery on Ulmus minor and Neoherpotrichiella juglandicola (incl. Neoherpotrichiella gen. nov.)from wood of Juglans regia. France, Aspergillus rouenensis and Neoacrodontium gallica (incl. Neoacrodontium gen. nov.)from bore dust of Xestobium rufovillosum feeding on Quercus wood, Endoradiciella communis (incl. Endoradiciella gen. nov.)endophyticin roots of Microthlaspi perfoliatum and Entoloma simulans on soil. India, Amanita konajensis on soil and Keithomyces indicus from soil. Israel, Microascus rothbergiorum from Stylophora pistillata. Italy, Calonarius ligusticus on soil. Netherlands , Appendopyricularia juncicola (incl. Appendopyricularia gen. nov.), Eriospora juncicola and Tetraploa juncicola on dead culms of Juncus effusus, Gonatophragmium physciae on Physcia caesia and Paracosmospora physciae (incl. Paracosmospora gen. nov.)on Physcia tenella, Myrmecridium phragmitigenum on dead culm of Phragmites australis, Neochalara lolae on stems of Pteridium aquilinum, Niesslia nieuwwulvenica on dead culm of undetermined Poaceae, Nothodevriesia narthecii (incl. Nothodevriesia gen. nov.) on dead leaves of Narthecium ossifragum and Parastenospora pini (incl. Parastenospora gen. nov.)on dead twigs of Pinus sylvestris. Norway, Verticillium bjoernoeyanum from sand grains attached to a piece of driftwood on a sandy beach. Portugal, Collybiopsis cimrmanii on the base of living Quercus ilex and amongst dead leaves of Laurus and herbs. South Africa , Paraproliferophorum hyphaenes (incl. Paraproliferophorum gen. nov.) on living leaves of Hyphaene sp. and Saccothecium widdringtoniae on twigs of Widdringtonia wallichii. Spain, Cortinarius dryosalor on soil, Cyphellophora endoradicis endophytic in roots of Microthlaspi perfoliatum, Geoglossum laurisilvae on soil, Leptographium gemmatum from fluvial sediments, Physalacria auricularioides from a dead twig of Castanea sativa , Terfezia bertae and Tuber davidlopezii in soil. Sweden, Alpova larskersii, Inocybe alpestris and Inocybe boreogodeyi on soil. Thailand, Russula banwatchanensis, Russula purpureoviridis and Russula lilacina on soil. Ukraine, Nectriella adonidis on over wintered stems of Adonis vernalis. USA, Microcyclus jacquiniae from living leaves of Jacquinia keyensis and Penicillium neoherquei from a minute mushroom sporocarp. Morphological and culture characteristics are supported by DNA barcodes.